Academic Success through Engagement and Trust Fostered by Professor Leadership Style - Minseong Kim; Nancy D. Albers; Tami L. Knotts (MDPI AG, 2023)
This study focused on professor leadership styles and investigated the impacts of various leadership characteristics on student academic performance as well as students' perceptions of class engagement and trust toward a professor. Using multiple leaderships styles to estimate a model of the relationship between faculty leadership styles and student outcomes provides for a broader view compared to previous research. The empirical results indicated that student perception of class engagement was significantly influenced by a professor's emotional leadership, Pygmalion leadership, and charismatic leadership. Further, student perception of trust toward a professor was significantly affected by the professor's transformational leadership, Pygmalion leadership, and charismatic leadership. Lastly, student academic performance was significantly impacted by class engagement. This research provides practical applications for enhancing student academic performance with the adoption of relevant leadership styles in higher education classes.